PENGEMBANGAN DASHBOARD INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN DAN PENGAMBILAN KEPUTUSAN - Diqy Fakhrun Shiddieq; Agna Hilyah (J-ENSITEC, 2024)
Interactive dashboards emerge as an effective solution to meet these needs by providing real-time visual displays of business performance and enabling users to explore data easily. Despite the increasing demand for interactive dashboards, many organizations still face challenges in developing and managing dashboards according to their needs. This study aims to develop an interactive dashboard for monitoring product sales that aligns with business objectives, using a case study of Adidas shoe sales with data obtained from www.keggle.com. The methodology employed in this research involves two processes: system analysis and system design. The findings of this research present a data analysis dashboard for Adidas shoe sales, including sales data, profit, revenue, and total sales data per month and per region for each product. The successful development of interactive dashboards is expected to provide significant benefits, including increased operational efficiency, cost savings, and enhanced competitiveness in the market